Clam‐like Cyclotricatechylene‐based Capsules: Identifying the Roles of Protonation State and Guests as well as the Drivers for Stability and (Anti‐)Cooperativity. Issue 8 (24th March 2020) - Mehta, Nisha; Abrahams, Brendan F.; Goerigk, Lars
Abstract: Cyclotricatechylene (ctcH6 ) is a bowl‐shaped macrocyclic compound that can be used as a building block for self‐assembled capsules. ctcH6 and its derivatives in various protonation states – here collectively labeled as CTC – form dimers that resemble the shape of a clam. These clam‐shaped entities have been studied experimentally by Abrahams, Robson, and co‐workers [B. F. Abrahams, N. J. FitzGerald, T. A. Hudson, R. Robson and T. Waters, Angew. Chem. Int. Ed . 2009, 48, 3129–3132] where the capsules acted as an excellent host for large alkali‐metal cations. In this study, we present a detailed analysis based on accurate dispersion‐corrected Density Functional Theory approaches that reveals the factors that stabilise such CTC‐based capsules at different protonation states and their interaction with various encapsulated guests. Our results show that the capsules' overall stability results as an interplay of hydrogen bonding, London dispersion, and electrostatic effects. The most stable capsules with group‐1 and group‐2 cations as guests contain only six phenolic hydrogens, as opposed to the maximum possible number of twelve. Inclusion of larger alkali‐metal cations is favoured due to larger London‐dispersion contributions. Cations are favoured as guests over isoelectronic neutral species, as the resulting host‐guest complexes experience additional stability due to cooperative effects. In fact, using the latter to drive the formation of specific capsules could be used in future strategies aimed at synthesising similar aggregates; our results provide an insightful understanding and useful guidance for such future endeavours. Abstract : The first comprehensive computational investigation of cyclotricatechylene‐based capsules is presented with emphasis on identifying ideal guests, protonation states, and the driving forces that favour capsule stability. The chosen computational methods are known for their reliability and have predictive character. The importance of cooperative and three‐body London‐dispersion effects is revealed. These findings support future synthesis and investigations of these and similar systems.